The efficiency of prophylactic Oral antibiotic after vaginal delivery in prevention of puerperal infection. - حسو, رموز; لينا رمضان; لؤي حسن (Latakia University Journal -Medical Sciences Series, 2022)
Objective: This search was designed to study the efficiency of prophylactic oral antibiotics after vaginal delivery compared to not giving them on the occurrence of puerperal infection. Patients and methods: This were a Randomized controlled trial (RCT)study conducted at obstetrics and Gynecology Department in Tishreen university Hospital Lattakia during the period between June 2021−June2022∙ Our study includes 206 patients divided into two groups Each group includes 103 patients They were compared∙ The first: was not giving antibiotics after vaginal delivery ∙ The second: was giving antibiotics before leaving the hospital∙ The antibiotic used was CEFIX 400 mg for week∙ The patient was informed of the symptoms of puerperal infection, And the need to return to the hospital when it happens∙ We studied the incidence of sepsis by comparing the two groups and the type of infection that occurs∙ Also, we studied Risk Factors for sepsis in both groups∙ Results: Results infection occurred in the first group37,9%comparison14,6% in the second group The puerperal endometritis, perineal wound infection, occurred less in second group p<0,05 The episiotomy infection, puerperal mastitis, urinary tract infection, occurred less in second group but not important p>0,05 ∙ Obstetrical status, degree of perineal tear, number of vaginal carious, labor duration, Risk factors for infection in both groups p<0,05∙ Amniotic fluid disturbing is not Risk factor p>0,05∙ Conclusion: We recommend giving prevention antibiotics to avoid occurrence of puerperal infection, and reducing the need for hospitalization, and economic cost∙